Transport and The Urban Environment : Proceedings of a Conference held by the International Economic Association at Lyngby, Denmark - Rothenberg, Jerome; Heggie, Ian Graeme; International Economic Association (London : Macmillan, 1974)
This book is a record of rather more than one half of the proceedings of the International Economics Association (IEA)-sponsored Conference on Urbanization and Environment. The subject matter is divided into two parts: One is concerned primarily with urban development and its impact on the environment; the other on more technical considerations about waste residuals, water quality management and pollution policy.
Includes bibliographies.
ne 21/02/2018
Loan
Keywords: Urban transportation; Urbanization; Urban ecology (Sociology)